The chronic leukaemias - Peter Jacobs; Lucille Wood (AOSIS, 1989)
The slow progression of both chronic granulocytic and lymphocytic leukaemia, when compared to their acute counterparts, has been used as an argument to support less aggressive therapy or even, in some instances, a watch-and-wait policy. This conservative approach is bolstered by a number of observations including the ease with which haematologic control can initially be achieved, the older age of patients with the lymphocytic variant and the paucity of controlled data showing that long disease-free survival or cure can result from the use of aggressive treatment. Given these circumstances, it is not surprising that many such individuals are managed outside specialised centres using a variety of agents and schedules, both of which may, on occasions, be inappropriate. Accumulating evidence suggests a need to reconsider these practices since cure is now possible in selected patients with chronic granulocytic leukaemia while the use of multi-drug regimens in the lymphatic form can significantly improve survival. These advances are the result of carefully conducted clinical trials involving many individuals the world over and constitute the basis fo r advocating early referral to those institutions where all the necessary expertise is available.